Retrospective Evaluuation of the Outcomes in the Patients with Chiari's Malformation Undergoing Surgical Treatment - Kaya, İsmail; Cingöz, İlker Deniz; Yüceer, Nurullah (International Journal of Scientific Research and Management (IJSRM), 2020)
Introduction and Objectives: We aimed at evaluating retrospectively effects of surgery on the clinical symptoms and signs and imaging parameters in the patients with Chiari's malformation undergoing surgical treatment.Materials and Methods: Medical charts and radiological images of the patients with Chiari's Malformation type I who had surgical treatment between January 2008 and July 2014 were reviewed retrospectively. The patients were classified as those having good (in whom the symptoms disappeared or reduced), stabilized (with preoperative symptoms persisting without any progression), or poor (with preoperative symptoms progressing in the postoperative period) outcomes.Findings: All patients underwent FMD, Cl laminectomy and duraplasty. Seventeen subjects underwent removal of arachnoid adhesions, 10 subjects underwent opening of the fourth ventricle, and one subject underwent subpial resection. Of the patients, 28 were female and 11 were male with ratio of females to males being 25:1. The youngest patient was 5 years old and the eldest one was 51 years old, and mean age of the patients was 3231 ± 3131 years. The subjects were divided in two groups based on presence or absence of associated syringomyelia: those with syringamyelia (Group 1, n = 15) and those without syringomyelia (Group 2, n = 24). Postoperatively, in the Group 1 (SM 1- CM) 10 (66.7%) patients had good, 3 (20%) had stabilized and 2 (133%) patients had poor surgical outcomes. In the Group 2, 23 (918%) subjects had good and 1 (4.2%) subject had stabilized outcomes. For the Group 2, rate of recovery was higher than in the Group 1 (918% and 66.7%, respectively; Pearson's chi-square test, P = 0.014). Rate of recovery in 21 subjects with degree of tonsillar herniation being more than 11 mm (95.2%) was statistically significantly higher than 18 subjects with degree of tonsillar herniation being less than 11 mm (72.2%) (Pearson's chi-square test, P = 0.047).Results: FMD is a safe and efficient surgical method for the Chiari malformations with or without associated syringomyelia. The subjects without associated syringomyelia benefited more from the surgery. Complications related to CSF may be reduced using additional tissue glues. Studies with greater number of cases should be conducted on the effect of degree of tonsillar herniation on surgical outcomes.